The Influence of Human Resource Development and Economic Growth on Poverty - Amigrah Mustain Mustain/Nasriati (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
The purpose of this study is to analyze the impact of Human Resources (HR) and economic growth on poverty in the Luwu Raya region, South Sulawesi. Despite improvements in economic growth indicators at both national and regional levels, uneven distribution of this growth often exacerbates inequality and worsens poverty conditions. This research utilizes panel data from 2011 to 2023 and employs multiple linear regression methods using EViews 10. The results indicate that HR has a significant and negative impact on poverty, where a 1% increase in HR quality reduces poverty by 7.39%. Conversely, economic growth shows a positive but not significant impact on poverty, suggesting that economic growth has not uniformly improved the welfare of the Luwu Raya population. Analysis using the Random Effect Model (REM) demonstrates that HR and economic growth together have a significant effect on reducing poverty levels. The coefficient of determination of 66.2% indicates that HR and economic growth variables can explain variations in poverty in Luwu Raya. The findings of this study are expected to assist policymakers in formulating more effective development strategies, particularly in improving HR quality to reduce poverty.